Strategic management of small firms in hostile and benign environments - Covin, Jeffrey G.; Slevin, Dennis P. (Strategic Management Journal, 1989)
Abstract This paper reports the results of a study designed to investigate the effective strategic responses to environmental hostility among small manufacturing firms. Data on environmental hostility, organization structure, strategic posture, competitive tactics, and financial performance were collected from 161 small manufacturers. Findings indicate that performance among small firms in hostile environments was positively related to an organic structure, an entrepreneurial strategic posture, and a competitive profile characterized by a long‐term orientation, high product prices, and a concern for predicting industry trends. In benign environments, on the other hand, performance was positively related to a mechanistic structure, a conservative strategic posture, and a competitive profile characterized by conservative financial management and a short‐term financial orientation, an emphasis on product refinement, and a willingness to rely heavily on single customers.